The Influence of Competence, Social Interaction and Work Procedures on Work Motivation and the Implications for the Quality of Work of Regional Revenue Agency Employees of Muara Enim Regency - Alvin Setiawan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The author conducted research with the aim of knowing and analyzing the effect of competence, social interaction and work procedures on work motivation and the implications for the quality of work of employees of the Regional Revenue Agency of Muara Enim Regency. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test. Analysis using Structural Modeling Equation (SEM) from software statistic AMOS. The results of this research are descriptive in order to describe the respondents' perceptions of each variable, it can be concluded that: Respondents' perceptions of employee competency variables at the Muara Enim Regency Regional Revenue Agency are relatively good. Respondents' perceptions of the Social Interaction variable of employees at the Regional Revenue Agency of Muara Enim Regency are relatively good. Respondents' perceptions of the Employee Work Procedure variable at the Muara Enim District Revenue Agency were relatively good. Respondents' perceptions of the employee work motivation variable at the Regional Revenue Agency of Muara Enim Regency are relatively good. Respondents' perceptions of the employee's work quality variable at the Muara Enim District Revenue Agency are relatively good. Factors that influence the work motivation of employees at the Muara Enim District Revenue Agency are competence and work procedures. Factors that influence the quality of work of employees at the Muara Enim District Revenue Agency are social interactions. The variable of work motivation is not a mediating/intervening variable that is good for competence, social interaction and work procedures on the quality of work at the Muara Enim District Revenue Agency.